Gaya Hidup Hedonisme Remaja Urban Dalam Novel Mariposa Karya Luluk HF - Dinda Nilma Lestari; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to explain the forms of hedonism lifestyle of urban teenagers, the factors that cause hedonism lifestyle of urban teenagers, and the impact of hedonism lifestyle of urban teenagers in Mariposa novel by Luluk HF. The teory used in this research is literary sociology theory. This type of research is literary research using descriptive method. The data source of this research is the novel Mariposa by Luluk HF. The results of this research are (1) there are three forms of hedonism lifestyle of urban teenagers, namely (a) activities, (b) interests, and (c) opinions. (2) The factors that cause the hedonism lifestyle of urban teenagers are divided into two, namely (a) internal factors are factors that encourage someone to do something that comes from within that person consisting of attitudes, personality, and self-consept and (b) external factors are factors that cause something to happen that comes from outside the individual, consisting of one, namely family. (3) The impact of hedonism lifestyle of urban teenagers divided into two, namely (a) being a pursuer of physical identity and (b) having a high taste.